Recommended Sampling Intervals for Arsenic in Private Wells. Issue 1 (18th June 2020) - Mailloux, Brian J.; Procopio, Nicholas A.; Bakker, Mark; Chen, Therese; Choudhury, Imtiaz; Ahmed, Kazi Matin; Mozumder, M. Rajib H.; Ellis, Tyler; Chillrud, Steve; van Geen, Alexander
Abstract: Geogenic arsenic in drinking water is a worldwide problem. For private well owners, testing (e.g., private or government laboratory) is the main method to determine arsenic concentration. However, the temporal variability of arsenic concentrations is not well characterized and it is not clear how often private wells should be tested. To answer this question, three datasets, two new and one publicly available, with temporal arsenic data were utilized: 6370 private wells from New Jersey tested at least twice since 2002, 2174 wells from the USGS NAWQA database, and 391 private wells sampled 14 years apart from Bangladesh. Two arsenic drinking water standards are used for the analysis: 10 µg/L, the WHO guideline and EPA standard or maximum contaminant level (MCL) and 5 µg/L, the New Jersey MCL. A rate of change was determined for each well and these rates were used to predict the temporal change in arsenic for a range of initial arsenic concentrations below an MCL. For each MCL and initial concentration, the probability of exceeding an MCL over time was predicted. Results show that to limit a person to below a 5% chance of drinking water above an MCL, wells that are ½ an MCL and above should be tested every year and wells below ½ an MCL should be tested every 5 years. These results indicate that one test result below an MCL is inadequate to ensure long‐term compliance. Future recommendations should account for temporal variability when creating drinking water standards and guidance for private well owners. Abstract : Article impact statement : Private wells should be tested for arsenic (1) every year if above ½ a maximum contaminant level, or (2) every 5 years if below ½ an MCL.